Perancangan dan Evaluasi User Interface Aplikasi Smart Grid Berbasis Mobile Application - F. Danang Wijaya; Rudy Hartanto; Edi Susilo (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
Smart grid mobile application is a modernization in the consumption of electric power. Based on current research on smart grid mobile applications, it has investigated to the monitoring function, regulating, and scheduling energy consumption only. In the other case, the process of selling and buying electrical power is not inspected yet. This paper designedthe user interface (UI) of smart grid mobile application in the process of selling and purchasing the electrical power. This combined Materials Design for Android (MDfA) with a design that adopts Common Element Sets (CES). The results of UI design were tested using usability and User Experience (UX). Usability test used System Usability Scale (SUS) and UX test used User Experience Questionnaire (UEQ). The results of usability testing obtained a score of 72 that was considered above average and included in the category "good". UX test in each aspect obtained a score as follows: attractiveness 1.925, perspicuity 1.975, efficiency 1.913, dependability 1.730, stimulation 1.938, and novelty 1.988. Overall UX testing results were included into the category "very good".